Designing for diverse museum visitors’ identity exploration around inventiveness - Kaplan, Avi; Garner, Joanna K.; Rush, Amani; Smith, Monica (Frontiers in Education, 2023)
Introduction This paper describes an initial phase of research to inform the design of Change YOUR Game—an exhibition at the Smithsonian National Museum of American History (NMAH) that aims to promote visitors’ inventiveness in STEM and in other life domains. The exhibition’s content focused on the history of inventions and innovations in sports. The research was framed by the Dynamic Systems Model of Role Identity (DSMRI) and by a set of design principles for promoting visitors’ agentic identity exploration: The PRESS Principles. Methods Five data collection sessions engaged participants in a virtual, simulated visit to an early rendition of the exhibition. Diverse groups of participants were prompted to consider the self-relevance of the exhibition content to their identities and how they have been and can be inventive in their lives. Results Four themes captured participants’ museum visitor role identities, varied readiness to engage in identity exploration of their inventiveness, and how these provided affordances and hindrances to participants’ engagement in identity exploration in the context of the simulated visit. The themes served as bases for design recommendations. Discussion The study highlights the potential of the DSMRI and PRESS design principles to address conceptual and methodological challenges of research that aims to inform environmental design of a context that is not yet in existence and that will be relatively fixed. The findings suggest recommendations for design as well as theoretical insights about museum visitor role identities and the contexts that may promote visitors’ active and agentic engagement in exploring their identities.